A Study of Learning Methods and their Impact on Improving the Quality of Quran Memorization - Hirawan, Robi; Julhadi, Julhadi (Ruhama : Islamic Education Journal, 2024)
Extracurricular activities in some educational institutions are seen as something less important, this view then has an impact on the treatment of extracurricular activities which is very significant compared to intracurricular activities. In line with that, the learning method is an element that has an important position in learning without exception to Quran memorization learning. Therefore, this study aims to reveal and examine in depth the use of methods in Quran memorization and its impact on quality. To find the research objectives described above, this study uses qualitative methods, while the data sources are Islamic Religious Education teachers at MTs Negeri 8 Padang Pariaman as key informants, several students selected by snowball sampling as additional informants. Data were collected from informants through observation, interviews and documentation studies. The results of the study prove that first, the methods used in learning Quran memorization as an extracurricular program at MTs Negeri 8 Padang Pariaman are quite varied, teachers use different methods by considering the conditions, the level of intelligence of students. Second, as an extracurricular, the tahfiz program at MTs Negeri 8 has not received serious attention from all resources at this institution, students consider it as an ordinary extracurricular that is not mandatory for all students to follow. Third, the use of various methods in teaching tahfiz at MTs Negeri 8 Padang Pariaman has a good impact on improving the quality of students' memorization. Keyword : Learning Methods, Tahfiz Alquran; Extracurricular